Pendampingan Penguatan Keagamaan Anak melalui Festival Anak Islam Desa Putuk Kampungbaru Nganjuk - Miksan Ansori; Alfin Maskur (Jurnal Pengabdian kepada Masyarakat Desa (JPMD), 2020)
The social environment of the current society that does not support religious planting for children should be adapted and solved by the community itself. Based on the context, this Community mentoring program is carried out and directed to provide a religious reinforcement for children through the Islamic Children's festival. This Community mentoring activity is considered quite successful to realize the community about current environmental conditions. In the mentoring also raised cooperation and good communication between researchers and society as well as the community participation of Putuk Kampungbaru Village is actively in the success of the program. The number of participating participants and the abilities that the child has shown at the time of the race also shows the success of learning to strengthen the religion for children. All participants are given prizes that win or lose show a thorough appreciation for the child to continue to carry out the religious activities that have full support from the family and society. The success of this program can also serve as a model of implementation of religious reinforcement elsewhere by adjusting the context.